A pilot study evaluating differences in muscle tissue saturation and blood flow between older adults with and without sarcopenia - Shoemaker, Marni E.; Pereira, Suzette L.; Mustad, Vikkie A.; Gillen, Zachary M.; McKay, Brianna D.; Lopez-Pedrosa, Jose M.; Rueda, Ricardo; Cramer, Joel T. (Frontiers in Endocrinology, 2025)
IntroductionTo optimize skeletal muscle function, adequate oxygen transport and nutrient delivery to the muscle is needed. Decreased blood flow with aging may result in reduced nutritive flow to muscle, which may be compounded by those with less muscle mass. The purpose of this study was to examine differences in muscle oxygen utilization and muscle blood flow between non-sarcopenic and sarcopenic adults during pre- and post-prandial periods and during aerobic and anaerobic exercise.MethodsTen older adults (mean±SD; age=72.4±4.9y; stature=167.5±7.6cm; body mass=71.6±12.2kg) were categorized as non-sarcopenic, and eight (age=82.9±11.4y; stature=165.7±4.5cm; body mass=70.3±8.0kg) were categorized as sarcopenic based on handgrip strength, body composition, and physical performance. Near-infrared spectroscopy (NIRS) was recorded pre-and-post consumption of a rapidly-digesting carbohydrate meal and during aerobic and anaerobic exercise. Deoxygenated hemoglobin (Hb)+myoglobin (Mb) (deoxyHb), Total Hb+Mb (THb) and muscle tissue oxygen saturation index (TSI) was measured using NIRS. Changes from baseline were calculated for deoxyHb and THb normalized to adipose tissue thickness (ΔdeoxyHbATT and ΔTHbATT).ResultsPost-prandial, non-sarcopenic individuals had 224% greater ΔTHbATT at 90 min (p=0.034) compared to sarcopenic and higher levels at 150 mins compared to baseline (p=0.004). Non-sarcopenia demonstrated greater ΔTHbATT at 90–120 mins than 15–60 min (p=0.018–0.047). During aerobic exercise, non-sarcopenic reported approximately 9% greater TSI compared to sarcopenic individuals (p=0.023–0.046). For anaerobic exercise, non-sarcopenic individuals saw 18%–49% lower values for ΔTHbATT at 80 and 100% compared to 60% and a 4% lower value at 100% compared to 80% of the exercise bout (p=0.034–0.043), while sarcopenic individuals experienced no change (p=0.122–0.512). Non-sarcopenia had 13% greater TSI than those with sarcopenia at 40% (p=0.026) and saw significant decreases over the anaerobic exercise bout (p=0.011–0.049) while TSI in the sarcopenic group remained unchanged (p=0.084–0.529).DiscussionSarcopenia demonstrated decreased oxidative capacity and blood flow detectable by NIRS, potentially contributing to metabolic dysfunction. While more research is needed, NIRS responses were distinct between sarcopenic and non-sarcopenic individuals post-prandial and during exercise. Nutrition and exercise interventions focusing on strategies to improve blood flow to promote muscle health are necessary to reduce sarcopenia and related-metabolic dysfunction progression with aging.Clinical trials registry numberNCT03701867, clinicaltrials.gov.